The quality of water for human consumption in the Tolima department, Colombia - Karol J. Briñez A; Juliana C. Guarnizo G; Samuel A. Arias V (Universidad de Antioquia, 2012)
Objective: to describe the quality of drinking water in urban areas of the Tolima department and its relationship to the reported incidence of hepatitis A, acute diarrheal disease and social indicators. Methodology: descriptive observational study using cross-sectional ecological databases (sivicap) and (sivigila) 2010. It was mean, median, standard deviation, proportion of reported incidence of municipalities of Tolima (n = 47), we used one-way anova and correlation analysis. Results:63.83% of the municipalities of Tolima had potable water. In the category of sanitary non-viable municipalities were classified: Ataco, Cajamarca, Planadas, Rovira, Valle de San Juan, and Villarrica. 27.7% of the municipalities showed coliform results. No association was found between the incidence of the diseases and water quality, statistically significant relationship was found between the coverage of water supply, sewerage, education and water quality. Discussion: it is necessary to improve water quality, expanding service coverage, epidemiological reporting and promotion of good hygienic practices.